The marvels - Selznick, Brian 1966- (Scholastic Press, 2015)
In 1766, a boy, Billy Marvel, is shipwrecked, rescued, and goes on to found a brilliant family of actors that flourishes in London until 1900...and nearly a century later, Joseph Jervis, runs away from home, seeking refuge with his uncle in London, and is captivated by the Marvel house, with its portraits and ghostly presences